Vegetarianism, depression, and the five factor model of personality. Issue 3 (4th May 2018) - Forestell, Catherine A.; Nezlek, John B.
ABSTRACT: This study investigated whether vegetarians and omnivores differ in their personality characteristics. We measured the five factor model of personality and depressive symptoms in vegetarians, who avoided meat and fish ( n = 276); semi-vegetarians, who ate some meat and/or fish ( n = 1191); and omnivores ( n = 4955). Although vegetarians and semi-vegetarians were more open to new experiences, they were more neurotic and depressed than omnivores. Neither conscientiousness nor agreeableness varied as a function of dietary habits. These findings contribute to our understanding about differences between vegetarians' and omnivores' personalities, which might help us better understand individual differences in food preferences.